2018
DOI: 10.1021/acs.jpclett.8b00248
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of Auger Recombination in Nanocrystals via Ligand-Assisted Wave Function Engineering in Reciprocal Space

Abstract: A limiting factor to the technological application of conventional semiconductor nanostructures is their fast Auger recombination time. Strategies to increase it have so far mostly focused on decreasing the electron-hole wave function overlap in real space through structural modifications involving either elongation or shell growth. Here we propose an alternative mechanism for Auger recombination suppression: a decrease in the overlap of electron and hole wave functions in reciprocal space.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
23
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 54 publications
0
23
0
Order By: Relevance
“…In the case of the ehh Auger recombination the rates also decrease but not so strongly: lg(τ −1 A(H) ) = 11.86, lg(τ −1 A(Cl) ) = 11.44 and lg(τ −1 A(Br) ) = 11.20. It should be noted also that strong reduction of the Auger recombination rates was theoretically shown by Califano [139] for GaSb NCs whose surfaces were passivated with atoms of electronegative elements.…”
Section: Auger Recombinationmentioning
confidence: 74%
“…In the case of the ehh Auger recombination the rates also decrease but not so strongly: lg(τ −1 A(H) ) = 11.86, lg(τ −1 A(Cl) ) = 11.44 and lg(τ −1 A(Br) ) = 11.20. It should be noted also that strong reduction of the Auger recombination rates was theoretically shown by Califano [139] for GaSb NCs whose surfaces were passivated with atoms of electronegative elements.…”
Section: Auger Recombinationmentioning
confidence: 74%
“…In the case of the ehh Auger recombination the rates also decrease but not so strongly: lg(τ −1 A(H) ) = 11.86, lg(τ −1 A(Cl) ) = 11.44 and lg(τ −1 A(Br) ) = 11.20. It should be noted also that strong reduction of the Auger recombination rates was theoretically shown by Califano 140 for GaSb NCs whose surfaces were passivated with atoms of electronegative elements.…”
Section: A Auger Recombinationmentioning
confidence: 74%
“…55 This well-benchmarked and accurate method has been used in the past to successfully predict a wide range of experimental features, including the extinction coefficients as a function of size in CdSe dots, 57 the size-dependent conduction and valence band edge energies in nanocrystals of different materials, 7 the exciton dynamics in CdTe 58 and InSb 59 colloidal dots, electron transfer rates in Cd chalcogenide nanocrystals, 60 Auger rates in CdSe nanocrystals, 61 and the electronic states properties of CdSe TPs. 30 Auger recombination times are calculated according to established procedures 61,62 with the difference that here a sizeand position-dependent dielectric constant ε in = ε(R), 53 was assumed within the TP (and ε out = 1, was assumed for its environment), instead of a regional screening with ε in = ε bulk and ε out = ε solvent . 62 We compared the results of the two approaches in CdSe spherical nanocrystals with similar diameters to the TPs considered here and found that the calculated lifetimes agree for ε out ≈ 2.5-3.5 (see Fig.…”
Section: Methodsmentioning
confidence: 99%
“…30 Auger recombination times are calculated according to established procedures 61,62 with the difference that here a sizeand position-dependent dielectric constant ε in = ε(R), 53 was assumed within the TP (and ε out = 1, was assumed for its environment), instead of a regional screening with ε in = ε bulk and ε out = ε solvent . 62 We compared the results of the two approaches in CdSe spherical nanocrystals with similar diameters to the TPs considered here and found that the calculated lifetimes agree for ε out ≈ 2.5-3.5 (see Fig. S5 ESI †), which includes the dielectric constants of the most commonly used solvents and capping groups.…”
Section: Methodsmentioning
confidence: 99%